2024
DOI: 10.1186/s12889-023-17468-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between nutrition literacy and eating behaviors among nursing students: a cross-sectional study

Pouya Mostafazadeh,
Mohammad Javad Jafari,
Mohammad Reza Mojebi
et al.

Abstract: Background Eating behavior is an essential aspect of life that can have long-term effects on health outcomes. Nutrition literacy is crucial for better health and well-being. It empowers individuals to make informed decisions about their nutrition and take control of their eating habits. Objectives This study aimed to assess the relationship between nutritional literacy and eating behavior among nursing students at the nursing faculties of Ardabil U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In our study, high fat intake is likely related to unhealthy dietary habits and eating behaviors, which are common among Iranian students (41). A crosssectional correlational study on 224 nursing students in Iran reported a significant relationship between nutritional literacy and eating behaviors among participants (42). Another study on 412 university students in Taiwan found that nutrition literacy significantly predicted healthy eating behavior (43).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, high fat intake is likely related to unhealthy dietary habits and eating behaviors, which are common among Iranian students (41). A crosssectional correlational study on 224 nursing students in Iran reported a significant relationship between nutritional literacy and eating behaviors among participants (42). Another study on 412 university students in Taiwan found that nutrition literacy significantly predicted healthy eating behavior (43).…”
Section: Discussionmentioning
confidence: 99%